Sentence and discourse - Guéron, Jacqueline (Oxford University Press, 2015)
"This book looks at the relationship between the structure of the sentence and the organization of discourse. While a sentence obeys specific grammatical rules, the coherence of a discourse is instead dependent on the relations between the sentences it contains. In this volume, leading syntacticians, semanticists, and philosophers examine the nature of these relations, where they come from, and how they apply. Chapters in Part I address points of sentence grammar in different languages, including mood and tense in Spanish, definite determiners in French and Bulgarian, and the influence of aktionsart on the acquisition of tense by English, French, and Chinese children. Part II looks at modes of discourse, showing for example how discourse relations create implicatures and how Indirect Discourse differs from Free Indirect Discourse. The studies conclude that the relations between sentences that make a discourse coherent are already encoded in sentence grammar and that, once established, these relations influence the meaning of individual sentences." - Resumé vydavatel
Keywords: diskurzivní analýza; mluvnice; komparativní mluvnice; syntax; discourse analysis; grammar; comparative grammar; sborníky; papers of several authors